Total iridoid glycoside extract of Lamiophlomis rotata (Benth) Kudo accelerates diabetic wound healing by the NRF2/COX2 axis - Xiaoyu Geng; Ying Wang; Huan Li; Liang Song; Chen Luo; Xiaojie Gu; Haixin Zhong; Huilin Chen; Xinzhu Chen; Jianwei Wang; Zheng Pan (Chinese Medicine, 2024)
Abstract Background Lamiophlomis rotata (Benth.) Kudo (L. rotata), the oral Traditional Tibetan herbal medicine, is adopted for treating knife and gun wounds for a long time. As previously demonstrated, total iridoid glycoside extract of L. rotata (IGLR) induced polarization of M2 macrophage to speed up wound healing. In diabetic wounds, high levels inflammatory and chemotactic factors are usually related to high reactive oxygen species (ROS) levels. As a ROS target gene, nuclear factor erythroid 2-related factor 2 (NRF2), influences the differentiation of monocytes to M1/M2 macrophages. Fortunately, iridoid glycosides are naturally occurring active compounds that can be used as the oxygen radical scavenger. Nevertheless, the influence of IGLR in diabetic wound healing and its associated mechanism is largely unclear. Materials and methods With macrophages and dermal fibroblasts in vitro, as well as a thickness excision model of db/db mouse in vivo, the role of IGLR in diabetic wound healing and the probable mechanism of the action were investigated. Results Our results showed that IGLR suppressed oxidative distress and inflammation partly through the NRF2/cyclooxygenase2 (COX2) signaling pathway in vitro. The intercellular communication between macrophages and dermal fibroblasts was investigated by the conditioned medium (CM) of IGLR treatment cells. The CM increased the transcription and translation of collagen I (COL1A1) and alpha smooth muscle actin (α-SMA) within fibroblasts. With diabetic wound mice, the data demonstrated IGLR activated the NRF2/KEAP1 signaling and the downstream targets of the pathway, inhibited COX2/PEG2 signaling and decreased the interaction inflammatory targets of the axis, like interleukin-1beta (IL-1β), interleukin 6 (IL-6), apoptosis-associated speck-like protein (ASC), cysteinyl aspartate specific proteinase1 (caspase1) and NOD-like receptor-containing protein 3 (NLRP3).In addition, the deposition of COL1A1, and the level of α-SMA, and Transforming growth factor-β1 (TGF-β1) obviously elevated, whereas that of pro-inflammatory factors reduced in the diabetic wound tissue with IGLR treatment. Conclusion IGLR suppressed oxidative distress and inflammation mainly through NRF2/COX2 axis, thus promoting paracrine and accelerating wound healing in diabetes mice. Graphical Abstract